(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2026)
This dossier celebrates 20 years of meetings and academic collaboration between researchers from Brazil and the United States. Since 2004, Brazilian and American professors have taken part in this important effort in the field of Communication, which has benefited generations of scholars by bringing together researchers from across the Americas in a very special academic partnership.